The validity of sentinel lymph node biopsy using dye technique alone in patients with gastric cancer - Rino, Yasushi; Takanashi, Yoshinori; Hasuo, Kimiatsu; Kawamoto, Masakazu; Ashida, Akio; Harada, Hiroshi; Inagaki, Daisuke; Hatori, Shinsuke; Ohshima, Takashi; Yamada, Roppei; Imada, Toshio (Hepato-gastroenterology, 2007)
We investigated whether sentinel lymph node biopsy using dye technique alone is useful or not in decision-making for less invasive surgery in patients with gastric cancer. The subjects were 43 patients who had undergone laparotomy for gastric cancer and consented to undergo sentinel lymph node biopsy using patent blue dye. The patients enrolled were 26 males and 17 females, with a mean age of 62.5 years. The tumor sites were upper third of the stomach in 14, middle third in 16, and lower third in 13 patients. The depth of invasion was mucosa in eight, submucosa in 19, muscularis propria in five, subserosa in five, and serosa in six patients. Total gastrectomy was performed in 12, subtotal gastrectomy in 28, and proximal gastrectomy in three patients. The mean number of sentinel lymph node biopsies per surgery was 3.5 +/- 4.1. We were able to perform blue node biopsy in 40 out of 43 patients, but could not find any blue nodes in three patients. Among the 40 patients in whom blue nodes were identified, 29 patients with no metastasis in blue nodes had no evidence of lymph node metastasis (NO). The depth of invasion was not deeper than subserosa in all these patients. Metastasis was observed in one out of the three patients in whom no blue nodes were found. When the depth of invasion was not deeper than the subserosa and blue nodes were identified, no metastases in either non-blue nodes or blue nodes could be found in the absence of metastatic blue nodes. Therefore, if the depth of invasion is not deeper than the subserosa in gastric cancer, metastatic search in blue nodes seems sufficient and less invasive surgery can be performed safely. Even when the invasion depth is not deeper than the submucosa, the tumor could be metastatic to Group 2 lymph nodes in patients in whom blue node biopsy revealed metastases. When metastasis is found in lymph nodes by intraoperative frozen section diagnosis, less invasive surgery for gastric cancer is not indicated.